Heifer calving rate is lowly heritable in Hereford cattle - Bradford, Heather L.; Moser, Daniel W.; Bormann, Jennifer M.; Weaber, Robert L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2014)
Reproductive failure is consistently a top reason for culling beef cows from the herd. Culling young females is very costly to commercial producers because a young female hasn’t generated enough income to pay for the cost of developing that female. One way to improve reproductive performance in the cowherd is through genetics. Although reproductive traits tend to be lowly heritable, genetic improvement can be made through selection. Beef producers traditionally have selected for increased scrotal circumference to improve female fertility. Scrotal circumference is an indicator trait and is positively correlated to female reproductive performance. Faster genetic improvement could be made by selecting for an easy-to-measure, economically relevant trait. The American Hereford Association’s whole-herd reporting program has enabled the collection of more difficult-to-measure phenotypes such as reproductive performance. Producers enrolled in the program must report the reproductive status of all breeding- age females on a yearly basis. This reporting system includes information such as if a female was exposed for breeding and if she calved the following year. Traits like heifer calving rate and the likelihood that daughters will calve as a heifer if they were retained as replacements can be developed based on the data reported by Hereford breeders. Our objective was to estimate the heritability of heifer calving rate, an economically relevant trait.
Keywords: Beef; Genetics; Calving rate